Ankle arthrodesis using a modified Masquelet induced membrane technique for open ankle fracture with a substantial osteochondral defect: A case report of novel surgical technique. Issue 11 (November 2019) - Oh, Yoto; Yoshii, Toshitaka; Okawa, Atsushi
Abstract: Reconstruction of a bone defect using the Masquelet induced membrane technique has been well described. However, there are few reports of arthrodesis using this technique. In this case report, we describe a modified Masquelet technique for ankle arthrodesis with nailing. The patient was a 32-year-old man who sustained an open fracture of the right ankle with a substantial osteochondral defect as a result of a fall. Immediately after the injury, a staged procedure using the Masquelet technique was planned. The bone defect was filled with bone cement in the acute stage, but replacement of the cement was needed 6 months after the injury because of a prolonged inflammatory reaction. Ten months after the injury, the bone cement was removed, and ankle arthrodesis was performed using an IM nail with a combination of autologous and artificial bone. As a modification of the Masquelet technique, the anterior surface of the transplant site was covered with a large but thin layer of cortical bone instead of suturing the incised membrane. At 1 year postoperatively, firm bony union was achieved and the implant was removed. At follow-up 3 years after his injury, the patient is able to walk, undertake physical work, and has no clinical signs of infection. Our experience suggests that a modified induced membrane technique may be useful when treating an open limb fracture with an extensive osteochondral defect where preservation of the joint is difficult and arthrodesis is considered.